The Influence of Training and Competency on Serviceman Performance - Anggun Suci Budiarti; Sulastri Sulastri; Muhammad Ichsan Hadjri; Zunaidah Zunaidah (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
The role of Servicemen is considered very important for the sustainability of PT Trakindo Utama, making us aware that the long-term success and excellence of a company depends on the importance of human resources, because many of the resources a company has can be imitated, except human resources. The purpose of the research is to determine the influence of training and competency on serviceman performance at PT Trakindo Utama Sumbagsel. The research method uses quantitative descriptive research. The research was conducted from July to December 2023. This research used data collection techniques through questionnaires, observations and interviews. The sample studied was 100 Serviceman respondents (Technicians and Senior Technicians) at PT Trakindo Utama Sumbagsel. The data analysis method uses multiple linear regression methods. The research results on the Training variable (X1) have a positive and significant influence on Serviceman Performance (Y) at PT Trakindo Utama Sumbagsel. The Competency variable (X2) does not have a positive and significant influence on Serviceman Performance (Y) at PT Trakindo Utama Sumbagsel. Companies need to review the training programs that have been created and provided to Servicemen to see whether they are in accordance with the wishes and needs of the Servicemen, because from this research there are Servicemen who are of the opinion that the training they have participated in is not in accordance with the wishes and needs of the Servicemen to improve their abilities to support work performance.Keywords: Training, Competence, Serviceman Performance